An Investigation of Mathematics Anxiety and Academic Coping Strategies Among High School Students in Vietnam: A Cross-Sectional Study - Luu-Thi, Huyen-Trang; Ngo-Thi, Thuy-Trinh; Nguyen-Thi, My-Tien; Thao-Ly, Thanh; Nguyen-Duong, Bao-Tran; Tran-Chi, Vinh-Long (Frontiers in Education, 2021)
Increasing numbers of students around the world are suffering from mathematics anxiety. The main objective of this study is to investigate the relationship between mathematics anxiety and gender, grade, career choices, and academic achievement in Grade 10, 11, and 12 students. This study used the Revised Version of the Mathematics Anxiety Rating Scale to survey 1,548 high school students (570 males and 978 females) from high schools in Vietnam. A multivariate analysis of variance (MANOVA) test, Pearson correlation and multiple linear regression were used to analyze data. The results show that there are significant differences in the influence of grade, academic achievement, and students’ career choices on mathematics anxiety. Academic coping strategies, gender, grade, and career choices are significant predictors of mathematics anxiety. Grade 12 students have higher levels of mathematics anxiety than others. Students with high average mathematics scores (9.0-10.0) have higher levels of mathematics anxiety than students with lower scores. Besides, students choosing finance and economics or industrial engineering to pursue into higher education also experienced higher levels of mathematics anxiety than others. This study contributes to the general discussion about the nature of mathematics anxiety and the relationship between mathematics anxiety and academic achievement.